Analysis of Factors from The Parties That Are The Source of Causes of Contract Change in Infrastructure Project in Tangerang City-Banten Province - Farihah, Iis Aisatul; Mahendra, Muhammad Oka; Mahendra, T.S. Hadi (POLITEKNIK NEGERI JAKARTA, 2024)
In the implementation of construction projects, problems cannot be avoided, one of which is contract change orders. This becomes a problem if it cannot be handled properly. Many factors cause change orders, including differences in understanding between stakeholders, owner requests, financial issues, scope differences, etc. SmartPLS software assessed and built a model with 13 causal change factors based on the literature review's structural relationships. The analysis technique in this research is the descriptive quantitative method. This method is used to obtain and examine structured and in-depth data that explains the behavior or circumstances being observed in depth and systematically. Data collected through the Google Form of 27 respondents to the Tangerang City PUPR Office project for improving and constructing city roads in the fiscal year 2023 were used in this study. In this study, two variables are the main focus in analyzing, in this case, the change order as an endogenous variable, and the project owner, contractor, and consultant as exogenous variables. The results of analysis using SEM-PLS found that the contractor variables have a significant effect on the occurrence of contract change orders by looking at the R-square value of 1.09 which can describe the amount of diversity that can be explained from the model built. The results of the analysis of the two types of variables are expected to be able to provide a comprehensive interpretation of the phenomenon of change orders that occur in the scope of construction, to take preventive action to prevent the occurrence of change orders, and researchers, the results of this study can be used as further study material to develop theories or related topics.